Spatial Analysis of Traffic Volume and Degree of Saturation in Shopping Center Corridors in Tuban District Using Geographic Information Systems - Bobby Ardianto; Fithri Estikhamah; Bagas Aryaseta (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
The development of retail centres in Tuban District significantly affects urban road performance. This study aims to analyze traffic volume and the degree of saturation (DS) around four major supermarkets: Citimall, Bravo, Samudra, and Keraton. Primary data were collected through field surveys on Mondays, Fridays, and Sundays during peak hours. Analysis using PKJI 2023 guidelines shows that Citimall has the highest traffic volume and DS of 0.673 on Sunday evenings. Statistical testing with One-Way ANOVA indicates a significant difference in traffic impact between locations (p < 0.001). Five-year projections using linear regression suggest that DS values at critical points, such as Citimall, will exceed capacity (DS > 1.0) without intervention. GIS mapping provides a visual representation of saturation hotspots, aiding in strategic traffic management. Contribution to Sustainable Development Goals (SDGs):SDG 9: Industry, Innovation and InfrastructureSDG 11: Sustainable Cities and SettlementsSDG 13: Climate Action